Portraying rhizobacterial mechanisms in drought tolerance: a way forward toward sustainable agriculture - Kaushal, M. (Elsevier, 2019)
Drought stress creates water deficit conditions which negatively affect physiological and biochemical processes that ultimately impede crop production. Recent research investigations have revealed that rhizobacterial inoculation of plants induces defense responses or drought tolerance in plants through various morphological and biochemical modifications resulting in enhanced tolerance to drought stress collectively referred as RIDER (rhizobacterial induced drought endurance and resilience). This review is an attempt to elucidate the understanding of RIDER mechanisms attributed by rhizobacteria in plants. Recent studies at molecular level revealed insights into the signaling networks of rhizobacterial interactions that contribute to drought tolerance. The RIDER mechanisms boost major physiological processes such as water uptake and source-sink relationships that enhance plant growth. This results in improved antioxidant activity, compatible solute accumulation that reduces osmotic stress caused by water deficit. In addition, phytohormonal modifications and extracellular rhizobacterial secretions also contribute to ensure plant survival during drought stress.